2017
DOI: 10.1038/nm.4443
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β plaques enhance Alzheimer's brain tau-seeded pathologies by facilitating neuritic plaque tau aggregation

Abstract: Alzheimer's disease (AD) is characterized by extracellular amyloid-β (Aβ) plaques and intracellular tau inclusions. However, the exact mechanistic link between these two AD lesions remains enigmatic. Through injection of human AD-brain-derived pathological tau (AD-tau) into Aβ plaque-bearing mouse models that do not overexpress tau, we recapitulated the formation of three major types of AD-relevant tau pathologies: tau aggregates in dystrophic neurites surrounding Aβ plaques (NP tau), AD-like neurofibrillary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
446
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(522 citation statements)
references
References 40 publications
34
446
1
2
Order By: Relevance
“…It is also possible that the rate of tau accumulation slows over time, similar to amyloid accumulation. [40][41][42] Thus, we hypothesized that PiB + OA would have higher rates of FTP accumulation than PiB − OA. Previous work has shown that cross-sectional FTP is associated with cross-sectional atrophy patterns in AD, 10,21 but our study extends these findings by revealing that FTP longitudinal accumulation occurs in regions that are relatively less affected by atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the rate of tau accumulation slows over time, similar to amyloid accumulation. [40][41][42] Thus, we hypothesized that PiB + OA would have higher rates of FTP accumulation than PiB − OA. Previous work has shown that cross-sectional FTP is associated with cross-sectional atrophy patterns in AD, 10,21 but our study extends these findings by revealing that FTP longitudinal accumulation occurs in regions that are relatively less affected by atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…2), an association not seen at high Thal phases. These results are correlative and not causal; nonetheless, the recent demonstration that pathological tau isolated from AD brain increases the plaque burden and induces widespread tau pathology in animal models implies that pathological tau interacts with the Aβ plaque environment to drive the increase in tau and Aβ pathology [17]. In particular, the increase from Braak stage III to IV may represent an important transition from age-associated pathology to dementia-associated pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of tau in mediating axonal damage and Aβ deposition seems to be linked to gain of function within the unique Aβ plaque environment. In a recent study, it was shown that tau initially aggregates in dystrophic neurites surrounding Aβ plaques (He et al , ). It is tempting to speculate that such initially formed tau species might locally compromise microtubules and thereby axonal transport of BACE1 and other proteins.…”
Section: Discussionmentioning
confidence: 99%